CHILEAN PATAGONIA. - Carte, Lindsey; Zunino, Hugo (Geographical Review)
In particular, her work is concerned with the salmon industry, which she argues has "transformed the lives and landscapes" of northern Patagonia over the last 40 years and continues to move deeper into Patagonia's waters. Keywords: Patagonia; Chile; territorio EN Patagonia Chile territorio 615 621 7 10/12/22 20221001 NES 221001 Patagonia evokes images of a remote, unpopulated frontier region endowed with a variety of undisturbed natural environments, including arid steppes, high mountains, fjords, forests, and ice fields. In general, Patagonia is considered to be located in the southern tip of South America between the Pacific and Atlantic oceans in the countries of Chile and Argentina. The Chilean state violently annexed the territories south of the Bío Bío River into what is perversely called the "Pacification of the Araucanía", and the Argentine government did much of the same through its "Conquest of the Desert" (Núñez [10]).